SATUS GIZI TIDAK SIGNIFIKAN MENENTUKAN PRESTASI SISWA SD - Vista, Dian; Delima E, Rosa; Hutasoit, Masta (Universitas Jenderal Achmad Yani Yogyakarta, 2014)
Background : The low Human Development Index (HDI) ranking in Indonesia compared with neighboring countries affected by the low nutritional status and health problems of Indonesiaâa population factor. One of the factorâs facing the health problemâs of Indonesian society is the problem of nutrition, undertrition and obessitas. They both have a negative impact on the quality of health. Governmentâs efforts to improve nutrition in school children by providing the Food Supplement Program School Children (PMT-AS). Good nutritional status is necessary for physical growth, brain development, employability and optimal health. Abnormalities that occur in the brain due to malnutritional have one impact is the decline in brain function that affects the ability to learn, resulting in lower childrenâs learning outcome. Objective : To determine the relationship of nutritional status and student achievement in elementary school Bangunjiwo Kasihan Bantul Yogyakarta. Methods : This study used non-experimental research methods with cross sectional approach. The population in this study were student in grade 6 in SD Negeri Bangunjiwo Kasihan Bantul. The samples used were 43 students. Engineering samples of the total sampling obtained a total sample of 43 students and analize using Spearman. Results : Nutritional status in elementary school Bangunjiwo Kasihan Bantul there are 36 students (83,7%) in the normal category of 43 respondents. A grade students achievement 6 in SD Negeri Bangunjiwo Kasihan Bantul most in categories as many 28 students (65,1%) of the 43 respondent. Conclusion : There was no significant association between nutritional status of student performance, with a value of ( p>0,05). Key words : Nutritional status, Learning achievement